MONETARY POLICY AND ENDOGENOUS MARKET STRUCTURE IN A SCHUMPETERIAN ECONOMY. (29th December 2014) - Chu, Angus C.; Ji, Lei
Abstract : This study develops a monetary Schumpeterian model with endogenous market structure (EMS) to explore the effects of monetary policy on the number of firms, firm size, economic growth, and social welfare. EMS leads to different results from previous studies in which market structure is exogenous. In the short run, a higher nominal interest rate reduces the growth rates of innovation, output, and consumption and decreases firm size through reduction in labor supply. In the long run, a higher nominal interest rate reduces the equilibrium number of firms but has no steady-state effect on economic growth and firm size because of EMS. Although monetary policy has no long-run growth effect, increasing the nominal interest rate permanently reduces the levels of output, consumption, and employment. Taking transition dynamics into account, we find that welfare is decreasing in the nominal interest rate and the Friedman rule is optimal in this economy.